2023
DOI: 10.1088/1748-605x/acb0a3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel hydrogel based on carboxymethyl chitosan/sodium alginate with the ability to release simvastatin for chronic wound healing

Abstract: Since wound dressing has been considered a promising strategy to improve wound healing, recent attention has been focused on the development of modern wound dressings based on synthetic and bioactive polymers. In this study, we prepared a multifunctional wound dressing based on carboxymethyl chitosan/sodium alginate hydrogel containing a nanostructured lipid carrier in which simvastatin has been encapsulated. This dressing aimed to act as a barrier against pathogens, eliminate excess exudates, and accelerate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…However, the mechanism of action of dECMMA/GelMA and its associated tissue healing signaling pathways remain unclear in this study [ 9 ]. Moreover, the fabrication process and optimization of the theoretical performance of this composite hydrogel require further investigation [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism of action of dECMMA/GelMA and its associated tissue healing signaling pathways remain unclear in this study [ 9 ]. Moreover, the fabrication process and optimization of the theoretical performance of this composite hydrogel require further investigation [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gel was then frozen at −20 °C and the samples were placed in a freeze-dryer and left overnight. The freeze-dried samples were cut open with a sharp knife to expose the interior of the gel, and the surface was coated with gold before being observed by SEM [ 9 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pure CMC film is highly swollen and unstable in the calcium chloride solution, indicating a weak interaction between CMC and Ca 2+ [ 36 ]. Therefore, other CMC crosslinkers are used, such as sodium alginate [ 36 , 37 , 38 ], oxidized sodium alginate [ 39 ], and genipin [ 40 ]. In the case of CMC/alginate, increasing crosslinking improves the degradation rate because of a larger number of hydrophilic NH 2 and COOH groups in the hydrogel matrix [ 41 ].…”
Section: Gelation Techniques Of Chitosan-based Hydrogelsmentioning
confidence: 99%
“…The composite exhibited efficient antibacterial activity against Staphylococcus aureus and Escherichia coli and indicated biocompatibility on mouse fibroblasts. The results of the study proved that the drug can be released over a prolonged period of time, which can be a major advantage in the wound healing process [ 199 ]. As recent studies have shown, an electrospun polycaprolactone/calcium alginate scaffold can be useful in skin tissue engineering.…”
Section: Alginate-based Materials: the State Of Innovationmentioning
confidence: 99%